1986
DOI: 10.1017/s0195941700065279
|View full text |Cite
|
Sign up to set email alerts
|

Double-Bagging of Items from Isolation Rooms is Unnecesary as an Infection Control Measure: A Comparative Study of Surface Contamination with Single- and Double-Bagging

Abstract: In many hospitals, waste materials and used linens from the rooms of patients in isolation or the clinical laboratories are routinely double-bagged to reduce contamination of the external surface of the bag that could be transmitted to hospital personnel subsequently handling them. No studies have prospectively examined the value, if any, of double-bagging. We randomly assigned waste and linens from the rooms of 42 patients in contact isolation to be transported in single bags or double bags. Shortly after a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 7 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The types of equipment investigated by the included studies included; carpet, (Anderson et al, 1982) laryngoscope blades, (Beamer & Cox, 1999) ventilation grilles (Kumari et al, 1998), curtains (Palmer, 1999), moving and handling equipment (Boden, 1999), general environmental contamination (Boyce et al, 1997), ultrasound probes (Ohara et al, 1998), staff pens (French et al, 1998) (Jones et al, 1995) linen bags, (Maki et al, 1986), staff homes (Masterton et al 1995) and dry mops (Oie & Kamiya, 1996). Anderson et al (1982) randomised patients to be cared for in either rooms with carpet floors or rooms with hard floors.They reported that S. aureus was isolated 26 times (44.8%) from carpets and 19 times (32.7%) from bare floors.…”
Section: Contaminated Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of equipment investigated by the included studies included; carpet, (Anderson et al, 1982) laryngoscope blades, (Beamer & Cox, 1999) ventilation grilles (Kumari et al, 1998), curtains (Palmer, 1999), moving and handling equipment (Boden, 1999), general environmental contamination (Boyce et al, 1997), ultrasound probes (Ohara et al, 1998), staff pens (French et al, 1998) (Jones et al, 1995) linen bags, (Maki et al, 1986), staff homes (Masterton et al 1995) and dry mops (Oie & Kamiya, 1996). Anderson et al (1982) randomised patients to be cared for in either rooms with carpet floors or rooms with hard floors.They reported that S. aureus was isolated 26 times (44.8%) from carpets and 19 times (32.7%) from bare floors.…”
Section: Contaminated Equipmentmentioning
confidence: 99%
“…Maki et al (1986) reported that 3/109 single thickness bags and 5/100 double thickness bags were contaminated with S. aureus. Although there was no statistical difference in the contamination with S. aureus between single bags and double bags that were used to dispose of waste and used linen, the results should be interpreted with caution as the single bags were made of thicker fabric than the double bags.…”
Section: Contaminated Equipmentmentioning
confidence: 99%
“…Highlighting the need for further study of contact transfer of pathogens in healthcare settings, a 2012 study of surface contamination in the general environment in three hospitals in Ontario, Canada identified the presence of five unique methicillin resistant S. aureus (MRSA) strains and eight C.difficile ribotypes in cultures from blood pressure machines, isolation carts, glove box holders, chair backs, and hand rails, among other locations (19). While a 1986 study of soiled linen and waste bags from patient isolation rooms reported comparable rates of positive surface cultures for the exterior surfaces of both single- and double-bagged waste and soiled linen, a significant limitation of that study was that cultures in this study were obtained after bags were set outside patients’ rooms, not after the bags had been manipulated repeatedly or stacked in collection trolleys with other bags that might be torn or spilled (20). …”
Section: Discussionmentioning
confidence: 95%
“…19 While a 1986 study of soiled linen and waste bags from patient isolation rooms reported comparable rates of positive surface cultures for the exterior surfaces of both single- and double-bagged waste and soiled linen, a significant limitation of that study was that cultures in this study were obtained after bags were set outside patients’ rooms, not after the bags had been manipulated repeatedly or stacked in collection trolleys with other bags that might be torn or spilled. 20…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, Neely et al 8 recorded the contamination of re-useable primary clinical waste containers, with S. aureus, enteric Gramnegative bacilli and P. aeruginosa on the outer surface of up to 25% of containers. These data are in accordance with the results of the present study, in which contamination with a range of potential pathogenic species was apparent in approximately one-third of bulk waste carts examined.…”
Section: Discussionmentioning
confidence: 99%